Let the social sciences evolve. Issue 4 (27th August 2014) - Smaldino, Paul E.; Waring, Timothy M.
Abstract We agree that evolutionary perspectives may help us organize many divergent realms of the science of human behavior. Nevertheless, an imperative to unite all social science under an evolutionary framework risks turning off researchers who have their own theoretical perspectives that can be informed by evolutionary theory without being exclusively defined by it. We propose a few considerations for scholars interested in joining the evolutionary and social sciences.